Evaluation of Wound Healing Activity of Methanolic Crude Extract and Solvent Fractions of the Leaves of Vernonia auriculifera Hiern (Asteraceae) in Mice - Lambebo MK; Kifle ZD; Gurji TB; Yesuf JS (Dove Medical Press, 2021)
Mulatu Kotiso Lambebo,1 Zemene Demelash Kifle,2 Tiruzer Bekele Gurji,3 Jibril Seid Yesuf2 1Department of Pharmacy, College of Medicine and Health Sciences, Hawassa University, Hawassa, Ethiopia; 2Department of Pharmacology, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 3Department of Pathology, School of Medicine, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Jibril Seid YesufDepartment of Pharmacology, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, P.O. Box: 196, Gondar, EthiopiaTel +251912016761Email nimt3579@gmail.comBackground: Medicinal plants play an important role in treating various diseases. Vernonia auriculifera Hiern is one of the medicinal plants used traditionally for the management of wounds. However, there were no scientific reports documented so far on the wound healing activities to substantiate the claim. Thus, the present study provides a scientific evaluation for the wound healing potential of the crude extract as well as solvent fractions of the leaves of Vernonia auriculifera Hiern.Methods: Extraction was carried out by maceration using 80% methanol and part of the crude extract fractionated with chloroform, ethyl acetate, and aqueous solvents. Simple ointment bases were prepared using hard paraffin, cetostearyl alcohol, white soft paraffin and wool fat according to British Pharmacopoeia. Then, two types of ointment formulations were prepared from the extract, ie, 5% w/w and 10% w/w. Mice and rats were employed for wound healing study and dermal toxicity test, respectively. Wound healing effects were evaluated by percent of wound contraction, period of epithelialization, tensile strength, and histological analysis as parameters in excision, incision, and burn wound models. Finally, the data were expressed as mean ± SEM, and the results were analyzed using one-way ANOVA followed by post hoc Tukey-test.Results: In the excision wound model, the 10% w/w crude extract ointment showed significant wound contraction (P < 0.001) from day 4 to day 18 as compared to the negative control. Both the 5% w/w (P < 0.001) and 10% w/w (P < 0.05) crude extract ointments have showed statistically significant difference in epithelialization period as compared to the negative control. Groups treated with the ethyl acetate and aqueous fractions ointments in incision wound model showed a statistically significant (P < 0.001) increase in tensile. The 10% w/w and 5% w/w ointments of the crude extract showed a significant (P < 0.001) increase in breaking strength compared to simple ointment and the untreated control groups. In burn wound model, significant reduction in epithelialization period was observed in 5% w/w (P < 0.05) and 10% w/w (P < 0.001), and the percentage of wound contraction was significantly increased in most of post wounding days by 10% w/w (P < 0.001) and 5% w/w (P < 0.05) crude extract ointments and compared to the negative control.Conclusion: The crude, aqueous, and ethyl acetate fraction of Vernonia auriculifera leaves possess wound healing activities. This finding justifies the use of the leaves of this plant for wound healing as claimed in the traditional medicine literature.Keywords: wound healing, Vernonia auriculifera Hiern, wound models, leaves, Ethiopia